Evaluating the effectiveness of low volume spray application using air-assisted knapsack sprayers in wine vineyards - Michael, Costas; Gil, Emilio; Gallart, Montserrat; Kanetis, Loukas; Stavrinides, Menelaos (My University, 2020)
We evaluated spray coverage on grape leaves and bunches by a high-volume sprayer (HVS), an air-assisted, low volume knapsack sprayer (LVS), and a motorized knapsack dust applicator modified to spray liquid formulations (common sprayer–CS). At the full development of the vine canopy 1400, 250 and 150 L ha−1 were applied via HVS, CS and LVS, respectively. Sprayer type, leaf or bunch orientation, leaf position and leaf side significantly affected spray coverage (P < 0.001). Mean spray coverage on leaves or bunches was below 21% for CS, and above 40 and 55% for LVS and HVS, respectively. Downy mildew leaf infection was below 5% throughout the season, with a significant effect of sprayer, time and an interaction between sprayer and time (P < 0.001). Grape berry moth damage did not differ between sprayers and the untreated control. The current work suggests that LVS might be a viable alternative to HVS, but further work is needed to establish whether differences in spray coverage affect biological efficacy.
Keywords: Lobesia botrana; Pesticide application methods; Plasmopara viticola; Spray deposition; Volume rate